Business students' experiences of technology tools and applications in higher education. (12th January 2020) - Dowling‐Hetherington, Linda; Glowatz, Matt; McDonald, Elanor; Dempsey, Audrey
Abstract : There has been much debate about the increasing use of technology in all learning, training and development contexts. In the case of higher education, although technology may not have fundamentally changed teaching practices, students report how several technologies and applications help with their learning, research and collaborative activities. Through a survey of business students at an Irish university, this paper examines their expectations and experiences of faculty usage of technology tools and applications. Although, on the surface, the findings provide some degree of confidence that students' expectations of technology usage are being met, students would, nonetheless, like to see faculty make even greater, and more effective, use of technology in the classroom. The study provides faculty with examples from students of technology usage that supports their learning and these examples may be useful for faculty when designing and delivering their courses. Beyond the higher education context, the research highlights some broader practical implications for training and development in a corporate setting.